Rare Causes of Arterial Hypertension and Thoracic Aortic Aneurysms—A Case-Based Review - Svetlana Encica; Adrian Molnar; Simona Manole; Teodora Filan; Simona Oprița; Eugen Bursașiu; Romana Vulturar; Laura Damian (Diagnostics, 2021)
Thoracic aortic aneurysms may result in dissection with fatal consequences if undetected. A young male patient with no relevant familial history, after having been investigated for hypertension, was diagnosed with an ascending aortic aneurysm involving the aortic root and the proximal tubular segment, associated with a septal atrial defect. The patient underwent a Bentall surgery protocol without complications. Clinical examination revealed dorso–lumbar scoliosis and no other signs of underlying connective tissue disease. Microscopic examination revealed strikingly severe medial degeneration of the aorta, with areas of deep disorganization of the medial musculo–elastic structural units and mucoid material deposition. Genetic testing found a variant of unknown significance the PRKG1 gene encoding the protein kinase cGMP-dependent 1, which is important in blood pressure regulation. There may be genetic links between high blood pressure and thoracic aortic aneurysm determinants. Hypertension was found in FBN1 gene mutations encoding fibrillin and in PRKG1 mutations. Possible mechanisms involving the renin–angiotensin system, the role of oxidative stress, osteopontin, epigenetic modifications and other genes are reviewed. Close follow-up and strict hypertension control are required to reduce the risk of dissection. Hypertension, scoliosis and other extra-aortic signs suggesting a connective tissue disease are possible clues for diagnosis.